Sistem Pendukung Keputusan Penerima Bantuan Rehabilitasi Rumah Tidak Layak Huni (RTLH) Dengan Menggunakan Weighted Product Pada Desa Pandanwangi - Dani Endy Tatama, Ihza; Imam Agung, Achmad; Zein Vitadiar, Tanhella (Inovate, 2020)
Rehabilitation of uninhabitable home is an assistance program issued by the government to deal with problems by renovating home. This research was conducted with the topic regarding the selection of recipients of home rehabilitation assistance uninhabitable home in Pandanwangi village. In process of selection of recipient of assistance, is still done manually so it takes a long time, and allows the occurrence of the human error factor at a time. The research aims to build computerized system that can help the selection process recipient of assistance. This research used action research method. This method consists of four stages: planning, action, observation and reflection. The process calculation using the model Weighted Product using the technique of multiplication to connect rating attribute, where the rating of each attribute needs to be raised to advance with the weights of the attributes concerned. The results of this research are decision support system that can help facilitate staff performance in make decisions process by referring to the results of a ranking model. The alternative ranking results state that the alternative named Sai has the highest value with a total value of 0.065215. From the accuracy test, accuracy level of the system was built reached 80%. Keywords: Decision Support System, Rehabilitation of Uninhabitable Home, Weighted Product.